Thucydides and Force - O'Sullivan, Rory (Trinity College Dublin. School of Histories & Humanities. Discipline of Classics, 2025)
I argue that the representation of events in Thucydides' Peloponnesian War is framed by an ontology and a representation, not of power, but force: if power is something we possess, force possesses us. There are forces, plural, in the sense of the means by which power may be exercised and sustained (e.g. violence, charisma, debt). But of every such means the internal constitution, the ontological composition, is such that eventually it transforms not only what it is exerted upon, but what exerts it: the means expands, reproduces, and grows ascendant. That is force, singular. By force I do not mean some higher will or thought that governs history like providence. Nor am I referring to any static nature or constant principle underlying change. Its sense is formal. Force is the process by which, in revealing itself to be different than it appeared, each individual means of subsistence, domination or enjoyment changes us and sets new terms for our existence.
APPROVED
Keywords: Ancient Greek Philosophy; Ancient Greek Literature; Thucydides